Assessing bottom sediment contamination with heavy metals in the Klaipėda port semi-closed bays / Klaipėdos uosto pusiau uždarų įlankų dugno nuosėdų užterštumo sunkiaisiais metalais vertinimas - Arūnas Galkus; Rimutė Stakėnienė; Kęstutis Jokšas; Lina Lagunavičienė (Journal of Environmental Engineering and Landscape Management, 2012)
The present paper reports the results obtained by investigation of surface bottom sediment contamination with Cu, Zn, Ni, Pb, Cr, Cd, Hg in three largest semi-closed bays of Klaipėda Port in 2008 and 2009. The concentrations of heavy metals and organic carbon same as the percentages of 6 granular fractions were determined at 41 stations. The contamination level was established by calculating the Nemerov's pollution index. The major factors responsible for sediment contamination with heavy metals and distribution patterns of discrete pollutants and different pollution areas were determined. By comparison of the obtained results with the results of 1998, the changes of sediment contamination with heavy metals in the last ten years were evaluated. It was determined that bottom sediments not contaminated with heavy metals are dominant in the semi-closed bays of Klaipėda port. Heavy contamination with nickel, and moderate contamination with zinc and copper only occur in small areas.